Application of Expert System With Forward Chaining Method in Detecting Infectious Diseases in Children - Mauliza Mauliza; Mutammimul Ula; Ilham Saputra; Rosya Afdelina; Muhammad Ikhsan (Science Midwifery, 2022)
Limited information about infectious diseases, especially diseases in children, is a major problem. The application of an expert system in detecting infectious diseases in children is needed in early detection in diagnosing diseases. The purpose of this study was to determine the diagnosis of infectious diseases in children based on the symptoms of the disease and the results of the diagnosis from the system for recommendations to patients with the type of disease suffered and the solutions provided. The stages of the research are collecting data and information on infectious diseases in children. The second is symptom and rule data collection. The third is making each solution from the types of diseases, and the last step is the solution for preventing infectious diseases in children, which is displayed in the system based on the analysis of disease rules. As for the variables in the application of disease tracing graphs, there are 17 rule graphs in detecting diseases in children. Analysis of the rules in the forward chaining method in disease detection for the types of symptoms of high fever (G001), sore throat and cough (G004), persistent hard cough that begins with a long breath through the mouth (G023), and diarrhea (defecation). watery more than three times per day (G030) Itching (G48), irritable and irritable (G033) The upper right abdominal area will feel pain, especially when pressed (G49). Analysis of each symptom G001, G004, G023, G030, G031, G033, G48, G49, the disease that will be detected is P009, namely Hepatitis A. The results obtained are in accordance with patient input by conducting a search using a rule model that utilizes a trace tree. forward based on tracing pediatric disease diagnoses with existing facts. The results of this study can display the results of diagnosis, disease analysis, solutions, and prevention based on the symptoms of the disease in children.